2022
DOI: 10.3389/fnins.2022.955096
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of thalamic network connectivity using transcranial direct current stimulation based on resting-state functional magnetic resonance imaging to improve hypoxia-induced cognitive impairments

Abstract: Hypoxic conditions at high altitudes severely affect cognitive functions such as vigilance, attention, and memory and reduce cognitive ability. Hence, there is a critical need to investigate methods and associated mechanisms for improving the cognitive ability of workers at high altitudes. This study aimed to use transcranial direct current stimulation (tDCS) to modulate thalamic network functional connectivity to enhance cognitive ability. We recruited 20 healthy participants that underwent hypoxia exposure i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…A retrospective, cross-sectional study revealed that people living at high altitudes had a higher incidence of depression than those living at low altitudes, suggesting that there was a statistically significant association between high altitude and depressive symptoms ( Zegarra-Rodriguez et al, 2022 ). Additionally, functional magnetic resonance imaging results showed that the emotional changes at high altitudes, including depression, fatigue, and energy levels, were related to connectivity between the limbic system ( Dalong et al, 2022 ). In this study, the open field test and elevated plus maze also found that mice in HAH group showed anxiety-like behavior.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective, cross-sectional study revealed that people living at high altitudes had a higher incidence of depression than those living at low altitudes, suggesting that there was a statistically significant association between high altitude and depressive symptoms ( Zegarra-Rodriguez et al, 2022 ). Additionally, functional magnetic resonance imaging results showed that the emotional changes at high altitudes, including depression, fatigue, and energy levels, were related to connectivity between the limbic system ( Dalong et al, 2022 ). In this study, the open field test and elevated plus maze also found that mice in HAH group showed anxiety-like behavior.…”
Section: Discussionmentioning
confidence: 99%
“…( Nelson et al, 2014 ; Douglas et al, 2015 ). In recent years, some reports showed that TDCS can increase local cerebral oxygen saturation, improve fatigue, enhance energy, and improve some plateau brain cognitive ability and plateau mental work ability to a certain extent ( Dalong et al, 2022 ).…”
Section: Therapymentioning
confidence: 99%